Implementasi dan Dampak Teknologi Autogate: Tinjauan Sistematis Lintas Sektor - Daniel Ricardo Hutagalung; Catur Susaningsih; Vita Nurul Fathya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Autogate technology is increasingly used to enhance efficiency and security in access control across various sectors. This study examines the implementation and impact of autogate through a Systematic Literature Review (SLR) using the PRISMA method. Data were collected from Google Scholar, OpenAlex, and CrossRef for 2020–2025. Of 65 eligible articles, 30 were analyzed further. The findings indicate that autogate speeds up identity verification, reduces queues, and improves user convenience. However, challenges such as high costs, complex system integration, and varying user acceptance remain significant. This study provides insights into autogate development and offers recommendations for optimizing its implementation.